Pengaruh Sistem Pengendalian Internal dan Kompetensi Sumber Daya Manusia terhadap Kualitas Laporan Keuangan UMKM di Kabupaten Lombok Barat - Agus Hermanto; Amiruddin Kalbuadi; Farha Farha; Isra Dewi Kuntary Ibrahim (Target : Jurnal Manajemen Bisnis, 2022)
This study aims to examine the effect of internal control systems and human resource competencies on the quality of financial reports for micro, small and medium enterprises (UMKM) in West Lombok Regency. The type of research used is associative because it examines the causal variables of independent and related variables. The research variables consist of the internal control system and the competence of human resources as independent variables and the quality of financial reports as the dependent variable. The research was conducted in West Lombok Regency using a survey sample method with a total of 135 respondents of micro, small and medium enterprises (UMKM) with a purposive sampling approach. Analysis of the research using test instruments in the form of validity testing with the Pearson product moment method and reliability testing with Croncbach's alpha. The feasibility test of the model uses classical assumption tests such as normality test, heteroscedasticity test and multicollinearity test. The analysis tool uses multiple linear regression analysis and hypothesis testing using t test for partial test and F test for simultaneous test. The results of the partial hypothesis test show that the internal control system and human resource competence on the quality of financial reports. In the simultaneous hypothesis test, the two independent variables affect the quality of financial statements. The limitation of this research is that the understanding of micro, small and medium enterprises (UMKM) related to the internal control system and competence of human resources in preparing financial reports is still low because most of the micro, small and medium enterprises (UMKM), both non-formal and formal, still associate the operational activities of micro, small and medium enterprises with owner's personal activities.